2004
DOI: 10.1177/1097196304042324
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Liquid Water Diffusivity from Transient Moisture Transfer Experiments

Abstract: The Boltzmann transformation method is used to determine the liquid water diffusivity from moisture content profiles as measured in a capillary water absorption experiment. An inter-laboratory comparison for analyzing the reliability of the determination method showed that the inaccuracy in the liquid water diffusivity is caused by scatter in the transformed data and by uncertainty in the boundary conditions at the intake surface and ahead of the steep moisture front. A methodology is proposed based on (1) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 6 publications
2
88
0
Order By: Relevance
“…Thermal diffusivity is reported to be sensitive to moisture content as well. Carmeliet et al [8] reported a reduction of 5 to 13% when the moisture content was doubled for brick and calcium silicate respectively. Jerman et al [9] reported a rate variation of water vapour permeability of 0.13 10 -6 m 2 /s for each 1% of change in RH for an aerated concrete with a water vapour permeability (dry cup) of 2.17·10 -6 m 2 /s.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal diffusivity is reported to be sensitive to moisture content as well. Carmeliet et al [8] reported a reduction of 5 to 13% when the moisture content was doubled for brick and calcium silicate respectively. Jerman et al [9] reported a rate variation of water vapour permeability of 0.13 10 -6 m 2 /s for each 1% of change in RH for an aerated concrete with a water vapour permeability (dry cup) of 2.17·10 -6 m 2 /s.…”
Section: Introductionmentioning
confidence: 99%
“…This can be done using gravimetric methods [17] or techniques such as nuclear magnetic resonance, c-ray attenuation, capacitance method or X-ray projection [2]. Several purposes can be served by these methods: extrapolation of the liquid conductivity from transient one-dimensional moisture uptake tests [18], observation of local variations of the flow speed due to fractures [19] or of the infiltration of chemicals, studies of reinforcement corrosion in concrete [8], etc. In the recent years, these techniques have been increasingly used in material sciences, and new operating methods were presented for their optimization and for a more efficient interpretation of their results.…”
Section: X-ray Radiographymentioning
confidence: 99%
“…As explained in [18], D w can be derived from transient 1D moisture profile measurements through a Boltzmann transform…”
Section: Hygric Characterizationmentioning
confidence: 99%
See 2 more Smart Citations